A Model for Adopting Sustainable Practices in Software Based Organizations - Jnr, Bokolo Anthony; Mazlina, Abdul Majid; Awanis, Romli (2017)
The present need for software organizations to seamlessly carryout software development objectives and aims results to significant high cost of electricity usage and the emission of CO2 in the environment and climate. Therefore there is need for software practitioners to adopt sustainable practices in software development process, when they utilized software to lessen electricity usage and reduce CO2 emission. Sustainable practice adoption is an attempt for software practitioners to tackle the current climatic problem, and can also improve the economic performance of software organizations. Software practitioners’ adoption of sustainable practices is beneficial to the society, climate and humanity. Existing approaches mainly focus on achieving sustainability when software practitioners develop software. Thus this paper contributes to sustainability research by presenting a model that offers an understanding of how software practitioners can adopt sustainable practices when they utilize software applications in software process. Findings from this paper show how Green practices can be diffused by software practitioners when they utilize software application in software organizations.